Psychosocial problems of schoolchildren and the psychological counseling approaches implicated by counselors for treating it - Abdullah, Mohammad Qassim (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
The aim of this study was to examine and evaluate the behavioral problems of schoolchildren in basic education stage and the psychological counseling approaches implicated by their counselor for treating it. In addition, assessing the differences in these approaches according to the variables of gender and educational qualification/degree. The sample consisted of (240) counselors (125 male, 115 female) enrolled from five educational administrations. The procedure has been used concluded Scale constructed for assessing the behavioral problems students and psychological counseling approaches used by counselors. The instrument's characteristics scored high level of validity and reliability. The findings showed that the most common behavioral problems were disobedience of teachers underachievement, aggression. In addition, the most counseling approaches used by counselors were individual and group counseling, Leisure time counseling, rational-emotive therapy, plying counseling, reality therapy, and client-centered therapy. According to the differences in counseling approaches relating to gender and academic qualification or degree of counselors, there were no significant differences except for the approaches of cognitive, behavioral and group counseling techniques and approaches.